Quantitative assessment of combination bathing and/or moisturizing regimens on skin hydration in atopic dermatitis - Chiang, Charles (2009)
BACKGROUND: Standard recommendations for skin care for patients with atopic dermatitis stress the importance of skin hydration and the application of moisturizers. However, there is little objective data to guide recommendations regarding the optimal practice methods of bathing and emollient application. OBJECTIVE: This study quantified cutaneous hydration status after various combination bathing and/or moisturizing regimens. METHODS: Four bathing/moisturizer regimens were evaluated in ten subjects, five pediatric subjects with atopic dermatitis and five subjects with healthy skin. The regimens consisted of bathing alone without emollient application, bathing and immediate emollient application, bathing and delayed application, and emollient application alone. Each regimen was evaluated in all subjects, utilizing a cross-over design. Skin hydration was assessed with standard capacitance measurements. RESULTS: In atopic dermatitis subjects, emollient alone yielded a significantly (p<0.05) greater mean hydration over 90 min (206.2% baseline hydration) than bathing with immediate emollient (141.6%), bathing and delayed emollient (141%), and bathing alone (91.4%). The combination bathing and emollient application regimens demonstrated hydration values at 90 minutes not significantly greater than baseline. Atopic dermatitis subjects had a decreased mean hydration benefit compared to normal skin subjects. CONCLUSIONS: Bathing without moisturizer may compromise skin hydration. Bathing followed by moisturizer application provides modest hydration benefits, though less than that of simply applying moisturizer alone.